Implementasi Sistem Informasi Implementasi Sistem Informasi Penelitian Dan Pengabdian Pada Fakultas Teknik Universitas Pelita Bangsa Berbasis Microservices: Information Systems, Microservices, Data Management, Research. - Dwi, M. Najamuddin; Agung, Fajar; Pramudito, Dendy K. (Jurnal Pelita Teknologi, 2024)
This study aims to develop and implement a microservices-based information system for managing research and community service data at Universitas Pelita Bangsa. The previous system had several shortcomings, including manual and fragmented data management, leading to data duplication, slow reporting processes, and limited access to information for lecturers. This research employed Agile Development methodology to ensure that the developed system effectively meets user needs. The results indicate that the implementation of a microservices architecture significantly improves the efficiency and effectiveness of data management, accelerates the reporting process, and facilitates easier access to information for lecturers. Additionally, the system optimizes collaboration among stakeholders by providing seamless and integrated access to research and community service data. Consequently, this microservices-based information system has proven capable of enhancing the quality of faculty services, while also offering flexibility for future system development in line with the faculty's needs and growth.